UPAYA MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MENGGUNAKAN PERMAINAN LOMPAT PADA SISWA KELAS V MI NURUL IMAN KENDALSERUT KECAMATAN PANGKAH KABUPATEN TEGAL TAHUN PELAJARAN 2013/2014 - Dedi Kisyanto (Universitas Negeri Semarang, 2015)
This study aims to determine that the use of learning the game jump in long jump squat style can improve student learning outcomes V class Kendalserut MI Nurul Iman. This study merupaka Action Research (PTK), which consists of two cycles. Peneliian was conducted in MI Nurul Iman Kendalserut with 40 students. Results of research use traditional two-cycle and four meeting showed in the first cycle of the average value of 76.06 by the end of class presentations learning ketuntansan 67.5% in the category baik.Sedangkan the second cycle of the average value of 87.11 by the end of class presentations mastery learning that 95% fall into the categories very high. It can be concluded the use of the game to jump on learning style long jump squat can improve student learning outcomes both in the realm of psychomotor, affective, and cognitive.